A distributed approach to the Optimal Power Flow problem for unbalanced and mesh networks. Issue 2 (2020) - Ferro, Giulio; Robba, Michela; D'Achiardi, David; Haider, Rabab; Annaswamy, Anuradha M.
Abstract: In the present paper we introduce a new distributed optimization approach to the solution of general Optimal Power Flow problem for unbalanced and mesh networks. A new convex formulation, based on McCormick Envelopes, is proposed with a decomposition profile and a distributed approach based on proximal coordination. The resulting algorithm is shown to converge with a rate of o (1/τ), where τ is the number of iterations. The approach is validated on a modified IEEE 13 bus network, with added distributed energy resources including distributed generation and demand response.